Altered Cervical Vestibular-Evoked Myogenic Potential in Children with Attention Deficit and Hyperactivity Disorder - Isaac, Valeria; Olmedo, Diego; Aboitiz, Francisco; Delano, Paul H. (Frontiers in Neurology, 2017)
Objective: Emerging evidence suggests that children with attention deficit and hyperactivity disorder (ADHD) present more difficulties in standing and walking balance than typically developing children. Most of previous studies have assessed these functions using postural and sensory organization tests showing differences in balance performance between control and ADHD children. However, to date it is unknown whether these balance alterations are accompanied with vestibular dysfunction. The principal aim of this study is to evaluate vestibular otolith function in ADHD and matched control children. Methods: We assessed vestibular otolith function in children with ADHD and controls using the subjective visual vertical (SVV) bucket test and cervical vestibular evoked myogenic potentials (cVEMP). In addition, gait and balance were evaluated using the dynamic gait index (DGI) and computerized posturography. Results: Non-significant differences between groups were obtained in SVV evaluation. DGI results show lower scores for overall test performance in children with ADHD (p<0.001), while computerized postural recordings showed significant differences for the limit of stability between groups (p=0.02). cVEMPs in response to 500 Hz tone bursts presented at 100dB were absent or reduced in children with ADHD, as revealed by differences in P1 and N1 peak-to-peak amplitudes between groups (p<0.01). Conclusion: These findings suggest that vestibular brainstem reflexes are altered in a subset of children with ADHD. We propose to include cVEMP reflexes in the clinical evaluation of ADHD patients.